2021
DOI: 10.1016/j.bpsgos.2021.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Liability to Cannabis Use Disorder and COVID-19 Hospitalization

Abstract: Background Vulnerability to COVID-19 hospitalization has been linked to behavioral risk factors, including combustible psychoactive substance use (e.g., tobacco smoking). Paralleling the COVID-19 crisis have been increasingly permissive laws for recreational cannabis use. Cannabis Use Disorder (CUD) is a psychiatric disorder that is heritable and genetically correlated with respiratory disease, independent of tobacco smoking. We examined the genetic relationship between CUD and COVID-19 hospitaliz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
(30 reference statements)
1
5
0
Order By: Relevance
“…Our study provides supporting evidence of a genetic association between several psychiatric disorders and COVID-19. This observation is in accordance with the findings of a study that revealed a positive genetic correlation between cannabis-use disorder and COVID-19 hospitalization using analyses of LD score regression of summarized GWAS results [ 31 ]. A considerable proportion of the general population has a history of psychiatric disorders (17–29%) [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our study provides supporting evidence of a genetic association between several psychiatric disorders and COVID-19. This observation is in accordance with the findings of a study that revealed a positive genetic correlation between cannabis-use disorder and COVID-19 hospitalization using analyses of LD score regression of summarized GWAS results [ 31 ]. A considerable proportion of the general population has a history of psychiatric disorders (17–29%) [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…Notably, the use of Cannabis was increased in U.S. and Canada by 6-8% during the COVID-19 pandemic in comparison to the pre-pandemic period [269], with a special increase among people with mental health [270]. Vulnerability to COVID-19 was correlated with genetic liability to Cannabis use disorder (CUD) [271].…”
Section: Anti-viral Activities Of Phytocannabinoidsmentioning
confidence: 99%
“…Intriguingly, the work by Hatoum et al. ( 18 ) also shows similarly complex relationships between genetic risk factors for cannabis use disorders and vulnerability to COVID-19 hospitalization, though these data did not indicate evidence for any direct causal effects of genetic risk for cannabis use disorder on COVID-19 hospitalizations.…”
mentioning
confidence: 79%